Resilience in Lesbian, Gay, and Bisexual Individuals. (November 2013) - Kwon, Paul
To promote psychological health among lesbian, gay, and bisexual (LGB) individuals, more comprehensive research on resilience factors in LGB individuals is needed. This article presents a theoretical framework based on the existing literature, with an eye toward guiding future research in this area. Social support clearly serves as a resilience factor for LGB individuals, in part through its ability to lower reactivity to prejudice. Social support is particularly effective when it specifically supports people's sexual orientation and is congruent with individuals' developmental needs. The ability to accept emotions and to process them in an insightful manner also buffers the negative impact of prejudice. In addition, hope and optimism allow LGB individuals to maintain psychological health when faced with prejudice.